2006
DOI: 10.1002/jnr.20857
|View full text |Cite
|
Sign up to set email alerts
|

Unconjugated bilirubin activates and damages microglia

Abstract: Microglia are the resident immune cells of the brain and are the principal source of cytokines produced during central nervous system inflammation. We have previously shown that increased levels of unconjugated bilirubin (UCB), which can be detrimental to the central nervous system during neonatal life, induce the secretion of inflammatory cytokines and glutamate by astrocytes. Nevertheless, the effect of UCB on microglia has never been investigated. Hence, the main goal of the present study was to evaluate wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 73 publications
3
41
0
Order By: Relevance
“…Interestingly, the secretion of IL-6 that was suppressed by UCB in astrocytes was slightly increased in neurons (7 pg/10 5 cells) and markedly enhanced in microglia (203 pg/10 5 cells). 18,38 Collectively, our data support the conclusion that microglia are the neural cells most responsive to UCB-induced release of cytokines.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Interestingly, the secretion of IL-6 that was suppressed by UCB in astrocytes was slightly increased in neurons (7 pg/10 5 cells) and markedly enhanced in microglia (203 pg/10 5 cells). 18,38 Collectively, our data support the conclusion that microglia are the neural cells most responsive to UCB-induced release of cytokines.…”
Section: Introductionsupporting
confidence: 82%
“…Microglia were also more vulnerable to UCB-induced apoptosis, revealing an increase of B2.6-and B4.5-fold when compared with astrocytes and neurons, and achieving levels of 11% over control values. 18,38 Recent studies have indicated that some molecules released by microglia may be harmful in acute brain insults and neurodegenerative diseases. 39 Therefore, we also looked for the ability of the three cell types to release glutamate, in particular microglia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive behavioral test battery is required in further studies to clarify whether Gunn rats have symptoms of the other psychiatric disorders. Unconjugated bilirubin has been shown to activate both microglia (Gordo et al., 2006) and astrocytes (Fernandes et al., 2011) in vitro. In accordance with, microglial activation and astrocytic activation in Gunn rats appear to be caused by high levels of unconjugated bilirubin, which can enter the brain as the free fraction (Ostrow, Pascolo, Shapiro, & Tiribelli, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This situation occurs following deposition of unconjugated bilirubin (UCB) in the central nervous system (CNS) owing to conditions leading to extreme UCB serum levels in the newborn (Hansen, 2002). UCB elicits nerve cell injury through interaction with cellular membranes (Rodrigues et al, 2002a), by triggering oxidative and nitrosative stress (Brito et al 2008a,b), and accumulation of extracellular glutamate Fernandes et al, 2004;Gordo et al, 2006;Silva et al, 1999), producing a widespread of structural and functional alterations that culminate in cell death Rodrigues et al, 2002b;Silva et al, 2002). We have shown that UCB elicits the release of pro-inflammatory cytokines, such as TNF-a and IL-1b, by neurons , astrocytes (Fernandes et al, 2004, and microglia , through the activation of MAPK (i.e., p38, JNK1/2 and ERK1/2) and NF-jB signaling pathways at the intracellular level (Brites et al, 2009;Fernandes et al, 2006Fernandes et al, , 2007a.…”
Section: Introductionmentioning
confidence: 98%